Tindak Pidana Korupsi Pasca Lahirnya Dewan Pengawas Komisi Pemberantasan Korupsi (KPK) - Nawir (Jurnal Hukum Lex Generalis, 2024)
The revision of Law No. 19 of 2019 which established the KPK Supervisory Board (Dewas) has sparked debate regarding its impact on the performance and independence of this anti-corruption institution. This topic is very relevant considering the decline in the KPK's performance in handling major corruption cases after the enactment of the law. This study aims to evaluate the effectiveness of the KPK Supervisory Board in supervising the institution and its impact on the success of corruption eradication. The method used in this study is a qualitative approach with in-depth interview techniques, document studies, and participant observation. Data were collected from interviews with legal experts, anti-corruption activists, and former KPK employees, as well as analysis of the KPK's annual report and related articles. The results of the study show that although the Dewas aims to increase accountability, its presence actually slows down the KPK's operational processes and reduces the effectiveness of corruption eradication. The Dewas' bureaucratic function risks affecting the KPK's independence, while the politicization of supervision worsens the internal conditions of the institution. This study suggests the need for an in-depth evaluation of the Dewas' role, as well as strengthening the KPK's operational flexibility to be more responsive to corruption. The implications of this study provide an important picture of the challenges faced by the KPK after the revision of the law, as well as recommendations for further research in examining institutional reform in Indonesia.